2007
DOI: 10.1007/s00572-006-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhiza communities of red oak (Quercus rubra L.) of different age in the Lusatian lignite mining district, East Germany

Abstract: Ectomycorrhizal (ECM) communities were assessed on a 720 m(2) plot along a chronosequence of red oak (Quercus rubra) stands on a forest reclamation site with disturbed soil in the lignite mining area of Lower Lusatia (Brandenburg, Germany). Adjacent to the mining area, a red oak reference stand with undisturbed soil was investigated reflecting mycorrhiza diversity of the intact landscape. Aboveground, sporocarp surveys were carried out during the fruiting season in a 2-week interval in the years 2002 and 2003.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 49 publications
4
52
1
1
Order By: Relevance
“…However, a dominance of only one species with more than 60%, as found in the Mumlavska hora plot, has seldom been reported and might indicate stressed environments. For example, up to 80% of roots were colonized by C. geophilum along a chronosequence of red oak stands on a forest reclamation site with disturbed soil in a lignite mining area (Gebhardt et al 2007). In a white spruce stand with high N deposition close to a fertilizer facility, Lactarius theiogalus dominated with a proportion of 69% (Lilleskov et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, a dominance of only one species with more than 60%, as found in the Mumlavska hora plot, has seldom been reported and might indicate stressed environments. For example, up to 80% of roots were colonized by C. geophilum along a chronosequence of red oak stands on a forest reclamation site with disturbed soil in a lignite mining area (Gebhardt et al 2007). In a white spruce stand with high N deposition close to a fertilizer facility, Lactarius theiogalus dominated with a proportion of 69% (Lilleskov et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of NGS DNA sequencing methods on Fagus sylvatica forest soils revealed that the most abundant fungal genera were Russula, Boletus, but also C. geophilum (Coince et al 2013). Moreover, C. geophilum was the main ECM fungus reported in root tip assessment in Q. rubra forests, although its abundance has oscillated significantly with tree age (Gebhardt et al 2007).…”
Section: Mycodiversity In Fagaceae Forest Ecosystemsmentioning
confidence: 99%
“…A common garden study evaluating pairs of native and non-native con-generics (species of Pinus and Quercus) found that, while the native Quercus hosted a more diverse EcM community than the non-native one, the opposite was true for the two Pinus taxa compared (Trocha et al 2012). Other studies focusing on non-native species have reported that introduced or invasive non-natives expediently recruit native EcM symbionts Gebhardt et al 2007;Tedersoo et al 2007;Kohout et al 2011;Bahram et al 2013), although the host establishment may be facilitated by co-introduction with compatible root symbionts (Tedersoo et al 2007;Vellinga et al 2009;Dickie et al 2010). …”
Section: Discussionmentioning
confidence: 99%